2021
DOI: 10.1111/cts.12983
|View full text |Cite
|
Sign up to set email alerts
|

First‐in‐human study of the safety, tolerability, pharmacokinetics, and pharmacodynamics of ALPN‐101, a dual CD28/ICOS antagonist, in healthy adult subjects

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 42 publications
(89 reference statements)
1
18
0
Order By: Relevance
“…It stands to reason then that forced expression of T cell co-stimulatory molecules at the tumor site could help fully activate endogenous tumor-infiltrating T cells. We constructed HDAds encoding either inducible T cell costimulator ligand (ICOSL), OX40L, or 41BBL, for which agonistic antibodies have been tested in clinical trials [ 42 , 43 ], and confirmed cancer cell surface expression of these molecules after infection ( Figure 2 D). To evaluate the proof-of-principle that HDAd-derived co-stimulatory molecules enhance the function of tumor associated antigen-specific T cells (TAA-T cells), we tested the ability of HD 41BBL to enhance the cytotoxicity of TAA-T cells, as 41BB is expressed on CD8+ T cells after activation [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…It stands to reason then that forced expression of T cell co-stimulatory molecules at the tumor site could help fully activate endogenous tumor-infiltrating T cells. We constructed HDAds encoding either inducible T cell costimulator ligand (ICOSL), OX40L, or 41BBL, for which agonistic antibodies have been tested in clinical trials [ 42 , 43 ], and confirmed cancer cell surface expression of these molecules after infection ( Figure 2 D). To evaluate the proof-of-principle that HDAd-derived co-stimulatory molecules enhance the function of tumor associated antigen-specific T cells (TAA-T cells), we tested the ability of HD 41BBL to enhance the cytotoxicity of TAA-T cells, as 41BB is expressed on CD8+ T cells after activation [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Subcutaneous KLH injection is the most frequently used administration route (21 out of 45 studies, Table 1 and Figure 2). (Curtis and Hersh, 1972;Brunner et al, 1973;Paty et al, 1975;Volkman et al, 1981;Ford and Burger, 1983;Bird et al, 1990;Ward et al, 1990;Snyder et al, 1993;Husby et al, 1994;Waldo et al, 1994;Fijter et al, 1996;Kantele et al, 1999;Rentenaar et al, 2002;Kraus et al, 2004;Miller et al, 2005;Kapp et al, 2010;Kantele et al, 2011;Hostmann et al, 2015;Belson et al, 2016;Giesecke et al, 2018;Yang et al, 2021) Other frequently used routes of administration include intramuscular and intradermal injections (Ashorn et al, 1986;Boelens et al, 2004;Birdsall and Rossen, 1983;Bird et al, 1990;Curtis and Hersh, 1972;Falconer et al, 1992;Ford and Burger, 1983;Kondratenko et al, 1997;Lange et al, 2003;Ochs et al, 1988;Otterhaug et al, 2021;Palestine et al, 1985;Powell et al, 1978;Salvaggio et al, 1969;Smith et al, 2004a;Smith et al, 2004b;Moldoveanu et al, 2004;Spazierer et al, 2009;…”
Section: Klh Immunization and Rechallengementioning
confidence: 99%
“…Analysis methods varied from enzyme-linked immunosorbent assay (ELISA) to hemagglutination assay (HA), radioimmunoassay (RIA), and cytometric bead array (CBA) (Table 2). The majority of the studies had used ELISA to quantify KLHspecific antibodies (Volkman et al, 1981;Palestine et al, 1985;Bird et al, 1990;Ward et al, 1990;Falconer et al, 1992;Husby et al, 1994;Waldo et al, 1994;Fijter et al, 1996;Kondratenko et al, 1997;Schuyler et al, 1997;Rentenaar et al, 2002;Lange et al, 2003;Smith et al, 2004a;Boelens et al, 2004;Smith et al, 2004b;Kraus et al, 2004;Moldoveanu et al, 2004;Miller et al, 2005;Spazierer et al, 2009;Kapp et al, 2010;Boulton et al, 2012;Milgrom et al, 2012;Hostmann et al, 2015;Poirier et al, 2016;Giesecke et al, 2018;Saghari et al, 2020;Otterhaug et al, 2021;Yang et al, 2021;Saghari et al, 2022).…”
Section: Assays For Quantification Of Systemic Humoral Responses Foll...mentioning
confidence: 99%
See 2 more Smart Citations